A video demonstration of the Li’s anastomosis—the key part of the “non-tube no fasting” fast track program for resectable esophageal carcinoma - Zheng, Yan; Li, Yin; Wang, Zongfei; Sun, Haibo; Zhang, Ruixiang (Journal of Thoracic Disease, 2015)
The main obstacle of fast track surgery for esophagectomy is early oral feeding. The main concern of early oral feeding is the possibility of increasing the incidence of anastomotic leakage. Dr. Yin Li used the Li’s anastomosis to ensure oral feeding at will the first day after esophagectomy. This safe and efficient anastomosis method significantly reduced the anastomotic leak rate, the number of post-operative days and stricture. Importantly, the “non-tube no fasting” fast track program for esophageal cancer patients was conducted smoothly with Li’s anastomosis. This article was focused on the surgical procedure of Li’s anastomosis.